The effect of leadership functions on team effectiveness of virtual teams - Matos, Alexandra Margarida Martins de (2018)
The purpose of this dissertation is the study of four different leadership functions on virtual teams and how can they impact differently the effectiveness of these teams. Data was collected from 332 employees. The results show that leadership functions in general are key for team leaders, it is through them that the leader structures all the work for the team. Additionally, the results indicate that being part of a virtual team or face-to-face team it is not statistically significant in terms of the impact of these functions in team effectiveness, since that when the leader works with leadership functions it will always lead to team effectiveness.